2003
DOI: 10.1109/jlt.2003.811425
|View full text |Cite
|
Sign up to set email alerts
|

Generation of complex microwave and millimeter-wave pulses using dispersion and kerr effect in optical fiber systems

Abstract: We study a new method to synthesize high-frequency complex microwave and millimeter-wave pulses using dispersion, Kerr effect, and group velocity delay in optical fiber systems. The profile of the generated pulses can be controlled by changing the parameters of the optical system. Nonlinear propagation effect in fibers can be used to generate electrical pulses with an extremely broad spread spectrum. Soliton trapping can be used to generate electrical pulses with a controllable frequency. Implicit results are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…ponents E x and E y are as follows: [4] Fig.2, Fig.3 and Fig.4 show that this proposed scheme can be used to generate 0-120 GHz microwave or millimeter-wave signal. For example, a 1550 nm initial non-chirped Gaussian optical pulse with the pulse duration T 0 = 1 ps is first fully polarization scrambled, then it is put into the polarization maintaining fiber with the fiber length L= 10 km, and we assume that the dispersion coefficient of the fiber 2 is -20 ps 2 km -1 , and the group velocity delay D is 15 ps, consequently, the signal with frequency of 23.87 GHz can be achieved.…”
Section: Fig1 System Diagram For the Generation Of Microwave And Milmentioning
confidence: 94%
“…ponents E x and E y are as follows: [4] Fig.2, Fig.3 and Fig.4 show that this proposed scheme can be used to generate 0-120 GHz microwave or millimeter-wave signal. For example, a 1550 nm initial non-chirped Gaussian optical pulse with the pulse duration T 0 = 1 ps is first fully polarization scrambled, then it is put into the polarization maintaining fiber with the fiber length L= 10 km, and we assume that the dispersion coefficient of the fiber 2 is -20 ps 2 km -1 , and the group velocity delay D is 15 ps, consequently, the signal with frequency of 23.87 GHz can be achieved.…”
Section: Fig1 System Diagram For the Generation Of Microwave And Milmentioning
confidence: 94%
“…When the laser acts on a fluid material composed of anisotropic molecules, the molecules will have different molecular polarizabilities and specular Kerr effects in different directions. The response time is about 10 −11 s-10 −12 s. [25][26][27]…”
Section: Nuclear Movementmentioning
confidence: 99%
“…Bordonalli et al [7] improved the above scheme and reported a MMW signal generation by combining optical sideband injection locking with optical phase-lock loop techniques for two fiber-coupled DFB lasers. Apart from the above continuous-wave microwave and MMW signal generation devices, Levinson et al [8] put forward a method of synthesizing complex frequency modulation form microwave and MMW pulses by using dispersion and Kerr effect in optical fiber systems, and demonstrated the generation of electrical pulses modulated at a controllable microwave frequency using a Mach-Zehnder interferometer and a chirped fiber grating. Very recently, they also demonstrated [9] a broad MMW modulated pulses generation with a linear frequency chirp by using two fiber Bragg gratings and a mode-locked fiber laser.…”
Section: Introductionmentioning
confidence: 99%